Adequate post-ischemic reperfusion of the mouse brain requires endothelial NFAT5 - Kunze, Reiner; Wacker, Paul; Breuer, Paula; Nasyrov, Emil; Kur, Ivan M.; Weigert, Andreas; Wagner, Andreas H.; Marti, Hugo; Korff, Thomas (Acta Neuropathologica Communications, 2024)
Severity and outcome of strokes following cerebral hypoperfusion are significantly influenced by stress responses of the blood vessels. In this context, brain endothelial cells (BEC) regulate inflammation, angiogenesis and the vascular resistance to rapidly restore perfusion. Despite the relevance of these responses for infarct volume and tissue recovery, their transcriptional control in BEC is not well characterized. We revealed that oxygen and nutrient-deprived BEC activate nuclear factor of activated T-cells 5 (NFAT5)—a transcription factor that adjusts the cellular transcriptome to cope with environmental stressors. We hypothesized that NFAT5 controls the expression of genes regulating the response of BEC in the ischemic brain. The functional relevance of NFAT5 was assessed in mice, allowing the conditional EC-specific knock-out of Nfat5 (Nfat5(EC)−/−). Cerebral ischemia was induced by transient middle cerebral artery occlusion (MCAO) followed reperfusion up to 28 days. While loss of endothelial Nfat5 did not evoke any phenotypic abnormalities in mice under control conditions, infarct volumes, neurological deficits and the degree of brain atrophy were significantly pronounced following MCAO as compared to control animals (Nfat5fl/fl). In contrast, MCAO-induced edema formation, inflammatory processes and angiogenesis were not altered in Nfat5(EC)−/− mice. RNAseq analyses of cultured BEC suggested that loss of NFAT5 impairs the expression of Kcnj2 encoding a potassium channel that may affect reperfusion. In fact, lower levels of KCNJ2 were detected in arterial endothelial cells of Nfat5(EC)−/− versus Nfat5fl/fl mice. Laser speckle contrast imaging of the brain revealed an impaired perfusion recovery in Nfat5(EC)−/− versus Nfat5fl/fl mice after MCAO.Collectively, NFAT5 in arterial BEC is required for an adequate reperfusion response after brain ischemia that is presumably dependent on the maintenance of Kcnj2 expression. Consequently, impairment of the protective role of endothelial NFAT5 results in enlarged infarct sizes and more severe functional deficits of brain functions.
Gesehen am 14.04.2025